bla(CTX–M–)(1)/IncI1-Iγ Plasmids Circulating in Escherichia coli From Norwegian Broiler Production Are Related, but Distinguishable - Mo, Solveig Sølverød (Front Microbiol, 2020)
Escherichia coli carrying bla(CTX–M–)(1) mediating resistance to extended-spectrum cephalosporins was recently described as a new genotype in Norwegian broiler production. The aim of this study was to characterize these isolates (n = 31) in order to determine whether the emergence of the genotype was caused by clonal expansion or horizontal dissemination of bla(CTX–M–)(1)-carrying plasmids. All included isolates were subjected to whole genome sequencing. Plasmid transferability was determined by conjugation, and plasmid replicons in the transconjugants were described using PCR-based replicon typing. Plasmid sizes were determined using S1 nuclease digestion. Plasmids in a subset of strains were reconstructed and compared to plasmids from broiler production in other European countries. The isolates belonged to nine different sequence types (STs), with the largest group being ST57 (n = 12). The vast majority of bla(CTX–M–)(1)-carrying plasmids were conjugative. All transconjugants were positive for the IncI1-Iγ replicon, and several also harbored the IncFIB replicon. Highly similar plasmids were present in different E. coli STs. Additionally, high similarity to previously published plasmids was detected. A reconstructed plasmid from an ST57 isolate harbored both IncI1-Iγ and IncFIB replicons and was considered to be co-integrated. The presence of one large plasmid was confirmed by S1 nuclease digestion. Our results show that dissemination of bla(CTX–M–)(1) in Norwegian broiler production is due to both clonal expansion and horizontal transfer of plasmids carrying bla(CTX–M–)(1). The bla(CTX–M–)(1)/IncI1-Iγ plasmids grouped into two main lineages, namely clonal complex (CC)-3 and CC-7. The genetic diversity at both strain and plasmid level indicates multiple introductions to Norway. We also show that the bla(CTX–M–)(1) plasmids circulating in Norwegian broiler production are highly similar to plasmids previously described in other countries.